Do Longer Operational Hours Affect Patient Loyalty? A Study of Facility Health Care in Bali, Indonesia - Adolf Gideon; Alifa Dimanti (Community Medicine and Education Journal, 2024)
In today's fast-paced society, healthcare services, especially at the primary level, are crucial for individuals with busy schedules. Patient loyalty, defined as the willingness to revisit a healthcare provider, is essential for healthcare facilities. Several factors contribute to patient loyalty, including satisfaction with services, the quality of facilities, and operational hours. This study investigates the relationship between clinic operational hours, patient satisfaction, clinic facilities, and patient loyalty in Bali, Indonesia. A quantitative study using a survey design was conducted. Data were collected from 124 respondents using a non-probability sampling technique. The questionnaire included items related to patient satisfaction, clinic facilities, operational hours, and patient loyalty. Data were analyzed using SmartPLS 4.0 to assess the relationship between the variables. The findings indicate that patient satisfaction, clinic facilities, and operational hours have a significant positive relationship with patient loyalty (P-value < 0.05). However, operational hours did not have a significant moderating effect on the relationship between patient satisfaction and clinic facilities and patient loyalty. In conclusion, while longer operational hours do correlate with increased patient loyalty, they do not amplify the impact of patient satisfaction or clinic facilities on loyalty. Healthcare facilities in Bali should prioritize patient satisfaction and quality facilities to foster loyalty.